Ledvina (Anatomical Chart Company - Wolters Kluwer, 1995)
Plastový plastický barevný plakát
Keywords: Juxtaglomerular Apparatus; ledviny; nefrologie; Nephrons; Kidney; nefrony; juxtaglomerulární aparát